2022
DOI: 10.5604/01.3001.0015.9599
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine companies’ reporting of information on actions towards achieving the Sustainable Development Goals

Abstract: Purpose: The aim of the research is to identify factors that influence companies' deci-sions about reporting on the achievement of Sustainable Development Goals (SDGs). Methodology/approach: A literature review allowed us to identify three potential factors that influence SDG reporting. The study used a sample of 8,499 companies. Data were obtained from the Refinitiv ESG Global database. Regression analysis was used to verify the research hypotheses. Findings: Engagement in social and environmental issues, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This is partly confirmed by another study, conducted on a sample of 8,500 companies from the Refinitiv ESG Global database. Its authors (Krasodomska et al, 2022) note that the three SDGs referred to by the most companies are Goal 8, Goal 13 and Goal 3. The fewest companies surveyed included Goal 14 in their reports (PwC, 2019).…”
Section: Sustainable Development Goals (Sdg)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is partly confirmed by another study, conducted on a sample of 8,500 companies from the Refinitiv ESG Global database. Its authors (Krasodomska et al, 2022) note that the three SDGs referred to by the most companies are Goal 8, Goal 13 and Goal 3. The fewest companies surveyed included Goal 14 in their reports (PwC, 2019).…”
Section: Sustainable Development Goals (Sdg)mentioning
confidence: 99%
“…This finding is consistent with the research by KPMG (2020 which found that the two SDGs focusing on addressing the global biodiversity challenge (Goal 14 and Goal 15) are the least relevant of all 17 SDGs for companies worldwide. It is noteworthy that, according to 61% of the companies surveyed, no SDGs are reported, and only 3% of the sample provide information on all 17 Sustainable Development Goals in their reports (Krasodomska et al, 2022). Thorlakson et al (2018) emphasise that the private sector mainly pays attention to workers' rights and compliance with local laws; and argue for the need to also integrate social and environmental issues into actions.…”
Section: Sustainable Development Goals (Sdg)mentioning
confidence: 99%
See 1 more Smart Citation